2015
DOI: 10.1080/10407782.2014.965095
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mixed Convective Heat Transfer in a Ribbed Channel Using the Lattice Boltzmann Method

Abstract: This article presents a two-dimensional (2D) numerical study on hydrodynamics and thermal transport in the presence of superimposed thermal buoyancy in a rectangular channel with staggered ribs mounted on both walls. This study is carried out for the Newtonian fluid at moderate Reynolds number. The Reynolds number is considered within the range (50 Re 120) with constant Prandtl number Pr ¼ 0.7, and mixed convective heat transfer is studied for Richardson number range 0 Ri 2. The unsteady 2D governing equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Biswas et al [18] 2D rectangular channel with staggered ribs. They studied steady and unsteady fluid flow and heat transfer characteristics, and found that beyond a certain critical Reynolds number, vortex shedding and mixing mechanisms enhance heat transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biswas et al [18] 2D rectangular channel with staggered ribs. They studied steady and unsteady fluid flow and heat transfer characteristics, and found that beyond a certain critical Reynolds number, vortex shedding and mixing mechanisms enhance heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The lattice Boltzmann method (LBM), a mesoscale method based on the discrete kinetic theory, has been developed over the past two decades as a powerful tool for simulating fluid dynamics and heat transfer problems [17][18][19][20][21][22][23]. Biswas et al [18] 2D rectangular channel with staggered ribs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus a large number of experimental [1][2][3] and numerical investigations mainly concentrated on an isolated single cylinder or two cylinders for pure forced convection and mixed convection. Particularly for the pure forced convection, several adjustable parameters such as the transverse separation ratio, the arrangement of circular or square cylinders, the attack angle, the blockage ratio, the power-law index, the Prandtl number, the Reynolds number and different inlet or wall boundary conditions, are regarded as vital factors to explore the flow and heat transfer mechanisms [4][5][6][7].In addition to the above adjustable parameters, the thermal buoyancy is also a crucial factor since the vortex patterns and the interactions between adjacent cylinders can change dramatically and further affect the flow dynamics and heat transfer efficiency [8][9][10][11][12][13][14]. For example, Sanyal and Dhiman [8] investigated the influences of the transverse gap ratio (0.7-10) and the Richardson number (0-1) for a flow through a pair of side-by-side square cylinders, and further gave a detailed explanation of the wake interaction phenomenon within a buoyancy-driven cross flow.…”
Section: Introductionmentioning
confidence: 99%